Numerical analysis of heat dissipation through granite and clay in the multibarrier system of a geological disposal facility - Kumar B.; Verma A.K.; Bajpai R.K.; Singh T.N. (My University, 2025)
High-level heat-emitting long-lived vitrified radioactive waste produced during recycling of the spent nuclear fuel is under consideration for permanent disposal in deep geological formations with appropriate thermomechanical, hydrogeological and geochemical properties. The capability of these rock formations ensuring long-term confinement and isolation of such waste from the environment is significantly controlled by their efficiency in smoothly dissipating the heat emanating from the waste. A number of rock types such as basalt, granite, clay stones, volcanic tuff, argillites, etc. are being evaluated worldwide as well as in India. In this study, a granite from Jalore and bentonite from Barmer, both from Rajasthan, India, have been evaluated for their heat dissipation capacity. The study revealed that the temperature within granite at the centre of the canister reached 55.21°C, resulting in a thermal stress of 25.50 MPa. Bentonite experienced a temperature of 67.42°C in the central part with maximum thermal stress and displacement of 1.78 MPa and 0.446 mm respectively. A displacement of 0.997 mm was recorded at the granite–bentonite interface. Thus, no significant microcrack formation or undesirable displacement was observed within the granite as well as in bentonite, suggesting their capability to isolate and confine the heat-emitting source for extended periods. © 2022, Current Science. All Rights Reserved.